2009
DOI: 10.1089/acm.2008.0497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Topical Vitamin B12 for the Treatment of Childhood Eczema

Abstract: Topical vitamin B(12) should be considered as a treatment option in children with eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The trial by Januchowski 218 also reported a significant decrease in eczema severity, measured using modified SCORAD scores (maximum of 27 points), for topical vitamin B 12 cream compared with the base cream after 4 weeks of treatment. Taking data from a graph, the decrease in total SCORAD scores for topical B 12 treatment after 4 weeks was 4.5 whereas that for the placebo treatment was 1.7 (p = 0.011).…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 94%
See 4 more Smart Citations
“…The trial by Januchowski 218 also reported a significant decrease in eczema severity, measured using modified SCORAD scores (maximum of 27 points), for topical vitamin B 12 cream compared with the base cream after 4 weeks of treatment. Taking data from a graph, the decrease in total SCORAD scores for topical B 12 treatment after 4 weeks was 4.5 whereas that for the placebo treatment was 1.7 (p = 0.011).…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 94%
“…The two trials 217,218 appear to show a significant beneficial effect of topical vitamin B 12 cream on the severity of eczema. The lack of CIs for the results presented in both trials means that there is no way to judge the statistical robustness of the results.…”
Section: Overall Implications For Research and Practicementioning
confidence: 95%
See 3 more Smart Citations